2011
DOI: 10.1074/jbc.m110.161893
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Regulation of Notch and Nuclear Factor of Activated T-cells (NFAT) c1 Transactivation in Osteoblasts

Abstract: Notch proteins are single pass transmembrane receptors that play a critical role in cell fate decisions. Notch regulates several developmental processes, and contributes to the regulation of cell renewal in multiple organs and cell systems (1). Notch is involved in skeletal development and homeostasis, because it inhibits chondrocyte proliferation and differentiation, and suppresses osteoblast differentiation and osteoclastogenesis (2-6). There are four Notch receptors (Notch1 to 4) and five canonical ligands,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
39
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 71 publications
8
39
1
Order By: Relevance
“…5). In accordance with the histomorphometric findings revealing no changes in osteoblast number or function in 1-month-old Notch2 Q2319X mice, Notch2 Q2319X mutant cells expressed no significant changes in Bglap and Alpl mRNA levels (7,17). In accordance with the increase in bone resorption observed in Notch2 Q2319X mice, expression of Tnfsf11 was increased in osteoblast- (Fig.…”
Section: Q2319xsupporting
confidence: 71%
See 1 more Smart Citation
“…5). In accordance with the histomorphometric findings revealing no changes in osteoblast number or function in 1-month-old Notch2 Q2319X mice, Notch2 Q2319X mutant cells expressed no significant changes in Bglap and Alpl mRNA levels (7,17). In accordance with the increase in bone resorption observed in Notch2 Q2319X mice, expression of Tnfsf11 was increased in osteoblast- (Fig.…”
Section: Q2319xsupporting
confidence: 71%
“…This canonical signaling pathway leads to the transcription of Hairy Enhancer of Split (Hes)1, -5, and -7 and Hes related with YRPW motif (Hey)1, -2, and -L. Skeletal cells express Notch1, Notch2, and low levels of Notch3 transcripts (13)(14)(15). Activation of Notch in undifferentiated and differentiated osteoblasts inhibits cell differentiation and function and causes osteopenia (16,17). In contrast, activation of Notch1 in osteocytes causes a pronounced increase in bone mass due to a suppression of bone resorption (18).…”
mentioning
confidence: 99%
“…Furthermore, recent studies have shown that Notch inhibited ATF4 transactivation and NFATc1 transcription, while NFATc1 reciprocally inhibited the transactivation of Notch target genes, suggesting that Notch and NFATc1 form a regulatory network to regulate the differentiation of osteoblasts (Zanotti et al 2011). Herein, we showed that T-MSCs constitutively express a higher level of ATF4 and NFATc1 than JB-MSCs, which is conversely correlated with the decreased expression of Notch3 in T-MSCs; knockdown of Notch3 expression led to increased expression of ATF4 and NFATc1 in JB-MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Hey1 bond to the promoter of NFATc1 and suppressed its expression. Expression of NFATc1 was increased in the bone of RBPjk deleted mice [81]. These results indicate that Notch signaling suppresses NFATc1 in osteoblasts to prevent excessive bone formation.…”
Section: Notch Signaling Regulates Nfatc1 and Nfatc2 In Osteoblastsmentioning
confidence: 51%
“…Twist, as a negative regulator of osteoblast, binds to RUNX2 and inhibits its ability to activate target genes. Notch and CCL8 and many other proteins not described here also regulate osteoblasts [80][81][82].…”
mentioning
confidence: 99%